Relationship between the association of rat epididymal protein "DE" with spermatozoa and the behavior and function of the protein - Cohen, Debora Juana (2000)
Rat epididymal glycoprotein DE associates with the dorsal region of the sperm head during sperm maturation, migrates to the equatorial segment (ES) with the acrosome reaction (AR), and is involved in gamete membrane fusion. In the present study we examined the association of DE with the sperm surface and the relationship of this interaction with the behavior and function of the protein. Cloning and sequencing of DE revealed a lack of hydrophobic domains and the presence of 16 cysteine residues in the molecule. Experiments in which cauda epididymal sperm were subjected to different extraction procedures indicated that while most of the protein is removable from sperm by mild ionic strength, a low amount of DE, resistant to even 2 M NaCl, can be completely extracted by agents that remove integral proteins. However, the lack of hydrophobic domains in the molecule and the failure of DE to interact with liposomes, does not support a direct insertion of the protein into the lipid bilayer. These results, and the complete extraction of the tightly bound protein by dithiothreitol, suggest that this population would correspond to a peripheral protein bound to a membrane component by strong noncovalent interactions that involve disulfide bonds. While ELISA experiments showed that no protein could be extracted by NaCl from capacitated sperm, indirect immunofluorescence studies revealed the ability of the NaCl-resistant protein to migrate to the ES. Together, these results support the existence of two populations of DE: a major, loosely bound population that is released during capacitation, and a minor strongly bound population that remains after capacitation, migrates to the ES with the AR, and thus would correspond to the one with a role in gamete fusion